ANALISIS FAKTOR PEMBENTUK KEPUTUSAN PEMILIHAN PERGURUAN TINGGI SWASTA PADA SEKOLAH TINGGI ILMU EKONOMI WIYATAMANDALA (STUDI EMPIRIS PADA MAHASISWA PRODI S1 MANAJEMEN DAN AKUNTANSI ANGKATAN 2018-2021 SERTA CALON MAHASISWA ANGKATAN 2022-2023) - Nur Hikmah; Sutrisno Sutrisno (Jurnal Bina Manajemen, 2022)
This study was conducted with the aim of knowing the Decision-Making Factors for the Selection of Private Universities at the Wiyatamandala School of Economics (Empirical Studies on Management and Accounting Undergraduate Students Class of 2018-2021 Prospective Students Class of 2022). Respondents in this study were active students of STIE Wiyatamandala class 2018-2021 and prospective new students of STIE Wiyatamandala class of 2022. Data collection was carried out through distributing questionnaires. The analysis technique used is multiple linear regression analysis. The results of the study show that External Factors, Campus Attributes, and Campus Efforts in Communicating with Students are variables that make students choose Private Universities at the Wiyatamandala Wiyatamandala School of Economics 2018-2021 and prospective students of STIE Wiyatamandala class of 2022-2023